Some Types of Introductory Formulas in Greek Klephtic (Heroic) Epic - Mutavdžić, Predrag J.; Đorđević, Saša B. (Balcanica - Annual of the Institute for Balkan Studies, 2013)
Certain types of introductory formulas typical of klephtic epic songs are synoptically demonstrated and analyzed. The introduction outlines the historical development of this category of folk songs, based on occasionally opposing views of literary historians and scholars concerned with the study of Greek folklore. The analysis, performed on a selected corpus of Greek klephtic epic songs, reveals basic structural principles that the anonymous folk singer abided by whilst composing these songs.